Study on Inoculum Doses of Corcyra cephalonica (Stainton) Eggs for its Efficient Mass Production in Laboratory - Bajracharya, Ajaya Shree Ratna; Bhat, Binu (Journal of the Plant Protection Society, 2024)
Rice moth, Corcyra cephalonica (Stainton) is a well-established factitious host for laboratory rearing of different egg parasitoids and predators. The insect is mass produced in ventilated plywood boxes with 2.5 kg of food medium in Nepal. In order to increase production efficiency of this rearing system, study was conducted to find optimum dose of egg inoculum. Replicated completely randomized experiment was conducted on crushed maize charging with 0.5, 0.33, 0.25 and 0.2 cc of egg inoculums at National Entomology Research Center during December 2022 to April 2023. Days to first adult emergence, adult emergence period, total adult and egg produced per box, body length and weight of moth, fecundity per female and 100 egg weight were recorded and analyzed using GenStat Discovery computer application. Days to first adult emergence did not differ significantly recording 54-55 days. The adult emergence period was found to increase with higher egg inoculum recording 63, 62, 49 and 42 days for 0.5, 0.33, 0.25 and 0.2 cc egg inoculums, respectively. Moth production was significantly higher in 0.33 cc (n = 1385) followed by 0.5 cc (n = 1169), 0.25 cc (n = 877) and 0.2 cc (n = 825) inoculums. Egg production was significantly highest in 0.33 cc (n = 75539) and remaining 0.5 cc (n = 71801), 0.2 cc (n = 72815) and 0.2 cc (n = 71801) were at par. The body length and weight of moths were found to decrease with increase in inoculum size and female moths were recorded bigger than male. The fecundity per female was higher in 0.25 cc (n = 371) and 0.2 cc (n = 363) followed by 0.3 cc (n = 271) and 0.5 cc (n = 260). The 100 egg weight did not differ among treatments recording 35-36 mg. The inoculum dose of 0.2 cc egg is suitable for efficient mass production of C. cephalonica.